Liquid activization while baking breads in breadmaker - Borodin, Vitaliy; Tsygankova, Anna (My University, 2013)
Methods of liquid activization while baking breads in breadmaker are considered.In practice new methods of activization allow to increase volume of bread to 50 % while baking breads from a grain mix.
Keywords: суміш зернова; хлібопічка; випікання хліба; кафедра вищої математики імені проф. Можара В. І.